ANALISIS NILAI-NILAI EDUKATIF PADA NOVEL AYAH KARYA ANDREA HIRATA - Sari, Nila (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to find out reviews about the novel and educative values on the novel of Ayah by Andrea Hirata. This research is a qualitative study using descriptive methods. The data source of this research is in the form of a journal related to research on novels and novels of Ayah by Andrea Hirata, amounting to 412 pages. Data collection techniques using listening and note taking techniques. Data validation techniques using data triangulation. Data analysis uses data reduction, data display and conclusion drawing. The results of this study indicate that there are educative values in Andrea Hirata Ayah novel that can provide benefits in social life and can be applied to life learning. The educational values contained in the novel are religious values, moral values, social values and cultural values